COACHING METHOD-BASED SUPERVISION MANAGEMENT TO IMPROVE TEACHERS' SOCIAL COMPETENCE IN ELEMENTARY SCHOOLS - Sugandi, Liawati; Wasliman, Eva Dianawati (Jurnal Konseling Pendidikan Islam, 2025)
This study examines the implementation of coaching-oriented supervision as a means to enhance the social competence of teachers at SD Negeri Tangkil and SD Negeri Cilongsong 1, situated in Cianjur Regency. Employing a qualitative methodology and a case study framework, data were obtained through in-depth interviews, direct observations, and document analysis. The data were processed through an iterative, interactive model, with triangulation applied to maintain research credibility. The findings reveal that supervision was planned through collaborative dialogue, executed in a reflective and egalitarian manner, and regularly evaluated to reinforce professional growth among teachers. The coaching-based supervision approach was shown to enhance teachers’ interpersonal communication, collaboration, and adaptability within the school environment. It is concluded that this strategy offers a meaningful pathway for advancing teachers’ social competence in a continuous and contextually grounded way. Accordingly, its broader application in the primary education context is highly recommended.